(CON)TEXTUAL MIGRATIONS, (CON)TEXTUAL ENCOUNTERS - Gjorgjieva Dimova, Marija (Philological Studies, 2019)
The subject of interest of this text is the film Elegy for you, interpreted through the prism of the relationships literature - history, text - context, discussed in the framework of the New historicism. Based on this theoretical-methodological background, the aim of film’s interpretation is to illustrate contextual moving of historical figures (in this case the Macedonian poet and revolutionary Kočo Racin), as well as to illustrate the possible creative games and semantic explosions created through a co-textually mediated meet between texts and contexts.